Investigation of Photon Attenuation Properties of CR-39 Lens - Eke, Canel; Yildirim, A. (HNPS Advances in Nuclear Physics, 2020)
The purpose of this study is to investigate photon attenuation parameters of Colombia Resin-39 (CR-39) lens, which are linear attenuation coefficient (LAC), mass attenuation coefficient (MAC), half value layer (HVL), tenth value layer (TVL), mean free path (MFP), effective atomic number (Zeff) and effective electron density (Neff). MACs were determined theoretically and with simulation in the energy range from 0.01 to 105 MeV. Also, obtained MACs of CR-39 lens were compared with MACs of pure aluminum and lead. Theoretically obtained Zeff values were compared with Zeff results obtained by the computer software. The results of this study are; a) the theoretically obtained MACs values are in agreement with MACs obtained results from simulation software, b) the theoretically obtained Zeff values are in agreement with Zeff obtained by the computer software c) the MACs of CR-39 lens are much lower than MACs of pure lead whereas there is not too much differences between MACs of CR-39 and pure aluminium d) the HVLs, TVLs and MFPs rise with increasing photon energy while the LACs and MACs reduce with increasing photon energy.